Identification of rare heterozygous linkage R965C‐R1309H mutations in the pore‐forming region of SCN5A gene associated with complex arrhythmia. Issue 5 (25th March 2021) - Lin, Yubi; Qin, Jiading; Shen, Yuhui; Huang, Jiana; Zhang, Zuoquan; Zhu, ZhiLing; Lu, Huifang; Huang, Yin; Yin, Yuelan; Wang, Ani; Jin, Lizi; Hu, Zhenyu; et al.
Abstract: Background: We examined the genetic background of a Chinese Han family in which some members presented with complex arrhythmias including sick sinus syndrome, progressive conduction block, atrial fibrillation, atrial standstill and Brugada syndrome. The possible underlying mechanism associated with the genetic mutation was explored. Methods: Targeted capture sequencing was conducted in the probands in the coding and splicing regions of genes implicated in inherited arrhythmias. Stable cell lines overexpressing wild type (WT) or mutant SCN5A were generated in HEK293T cells. Whole‐cell recording was performed to evaluate the functional changes in sodium channels. Results: The rare heterozygous linkage mutations, SCN5A R965C and R1309H, were found in these patients with complex familial arrhythmias. Compared to WT, R965C or R1309H, the peak current of sodium channel was dramatically reduced in HEK293T cell with linkage R965C‐R1309H mutation when testing potentials ranging from −45 to 15 mV. Notably, the maximum peak current of sodium channels with R1309H and linkage R965C‐R1309H displayed significant decreases of 31.5% and 73.34%, respectively, compared to WT. Additionally, compared to R965C or R1309H alone, the linkage mutation R965C‐R1309H demonstrated not only a more obvious depolarisation‐shifted activation and hyperpolarisation‐shifted inactivation, but also a more significant alteration in the time constant, V1/2 and the slope factor of activation and inactivation. Conclusions: The linkage mutation SCN5A R965C‐R1309H led to a more dramatically reduced current density, as well as more significant depolarisation‐shifted activation and hyperpolarisation‐shifted inactivation in sodium channels than R965C or R1309H alone, which potentially explain this complex familial arrhythmia syndrome. Abstract : The rare hereditary disease with complex arrhythmia syndrome resulted from the heterozygous linkage SCN5A R965C‐R1309H mutation, detected by targeted capture sequencing. The linkage mutation SCN5A R965C‐R1309H led to a more dramatic reduction in the current density of sodium channel, more depolarisation‐shifted activation and more hyperpolarisation‐shifted inactivation than either single mutation, R965C or R1309H, indicating synergistic effects on the pore‐gating properties of sodium channels, as detected by whole‐cell recordings.